Unconventional supercapacitors from nanocarbon-based electrode materials to device configurations - Liu, Lili; Niu, Zhiqiang; Chen, Jun (Chemical Society reviews, 2016)
As energy storage devices, supercapacitors that are also called electrochemical capacitors possess high power density, excellent reversibility and long cycle life. The recent boom in electronic devices with different functions in transparent LED displays, stretchable electronic systems and artificial skin has increased the demand for supercapacitors to move towards light, thin, integrated macro- and micro-devices with transparent, flexible, stretchable, compressible and/or wearable abilities. The successful fabrication of such supercapacitors depends mainly on the preparation of innovative electrode materials and the design of unconventional supercapacitor configurations. Tremendous research efforts have been recently made to design and construct innovative nanocarbon-based electrode materials and supercapacitors with unconventional configurations. We review here recent developments in supercapacitors from nanocarbon-based electrode materials to device configurations. The advances in nanocarbon-based electrode materials mainly include the assembly technologies of macroscopic nanostructured electrodes with different dimensions of carbon nanotubes/nanofibers, graphene, mesoporous carbon, activated carbon, and their composites. The electrodes with macroscopic nanostructured carbon-based materials overcome the issues of low conductivity, poor mechanical properties, and limited dimensions that are faced by conventional methods. The configurational design of advanced supercapacitor devices is presented with six types of unconventional supercapacitor devices: flexible, micro-, stretchable, compressible, transparent and fiber supercapacitors. Such supercapacitors display unique configurations and excellent electrochemical performance at different states such as bending, stretching, compressing and/or folding. For example, all-solid-state simplified supercapacitors that are based on nanostructured graphene composite paper are able to maintain 95% of the original capacity at a 180° folding state. The progress made so far will guide further developments in the structural design of nanocarbon-based electrode materials and the configurational diversity of supercapacitor devices. Future developments and prospects in the controllable assembly of macroscopic nanostructured electrodes and the innovation of unconventional supercapacitor configurations are also discussed. This should shed light on the R&D of supercapacitors.